How does female entrepreneurship affect happiness? - Sabrina Chikh-Amnache; Nabila Chikh-Boubaghela; Lotfi Mekhzoumi (Central European Economic Journal (CEEJ), 2023)
The purpose of this paper is to investigate the correlation between female entrepreneurship and happiness within the Association of Southeast Asian Nations (ASEAN) region. The study uses a panel data model with two independent variables measuring female entrepreneurship and five control variables measuring the determinants of happiness. The method used for analysis is the panel fixed effects of the method of moments quantile regression (MM-QR) to examine data from nine ASEAN countries between 2006 and 2021. MM-QR can capture the location and scale of the conditional distribution of the dependent variable, making it suitable for studying the heterogeneous effects of female entrepreneurship on happiness across happiness quantiles. This approach controls for unobserved time-invariant heterogeneity, reducing omitted variable bias in cross-sectional studies. The MM-QR approach is rigorous and robust for analysing the complex relationship between female entrepreneurship and happiness in ASEAN countries. The main contribution of this study is to shed light on the relationship between female entrepreneurship and happiness, which reinforces and supports comprehensive development in emerging countries. The findings suggest that policymakers and practitioners can benefit from supporting female entrepreneurship by implementing policies and programs that provide access to education, training, mentorship, and financing. Furthermore, the study highlights the importance of the gender development index (GDI) as a determinant of happiness in ASEAN countries.
Keywords: C23; I31; J16; L26; 330; entrepreneurship; female entrepreneurs; happiness; method of moments quantile regression; Southeast Asia countries